Mobile, Wireless, and Sensor Networks 2005
DOI: 10.1002/0471755591.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and Connectivity Issues in Wireless Sensor Networks

Abstract: Wireless sensor networks [33,34] have inspired tremendous research interest in since the mid-1990s. Advancement in wireless communication and microelectromechanical systems (MEMSs) have enabled the development of low-cost, lowpower, multifunctional, tiny sensor nodes that can sense the environment, perform data processing, and communicate with each other untethered over short distances. A typical wireless sensor network consists of thousands of sensor nodes, deployed either randomly or according to some predef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 73 publications
0
36
0
Order By: Relevance
“…In some studies coverage of each sensor will decrease with increasing the distance from sensor. Equation (1) shows sensor sensitivity values S of sensor S i at point P; ( , ) d S P i is the Euclidean distance between sensor and the point, λ is a positive parameter and γ is between 2 to 5 related to environment features [13].…”
Section: Coveragementioning
confidence: 99%
“…In some studies coverage of each sensor will decrease with increasing the distance from sensor. Equation (1) shows sensor sensitivity values S of sensor S i at point P; ( , ) d S P i is the Euclidean distance between sensor and the point, λ is a positive parameter and γ is between 2 to 5 related to environment features [13].…”
Section: Coveragementioning
confidence: 99%
“…For the k-coverage problem, formulated as a decision problem, polynomial-time algorithms (in terms of the number of sensors) are presented in [9]. A comprehensive study on both coverage and connectivity issues can be found in [8].…”
Section: Related Workmentioning
confidence: 99%
“…They are usually deployed in a wireless network to monitor and collect physical and environmental information such as motion, temperature, humidity, pollutants, and traffic flow in a given area (Romer and Mattern, 2004) . The information is then communicated to a processing center, where they are integrated and analyzed for different applications (Ghosh and Das, 2006). Capturing information of the environment is an important function of Wireless geoSensor Network (WSN) applications.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the area-based coverage problem, which is the concern of this paper, the objective is to obtain the maximum region covered by geosensors, and is usually evaluated as the ratio of the covered area to the whole area (Huang and Tseng, 2005). The area-based coverage calculation methods are classified into: (i) the methods that consider a raster environment (Akbarzadeh et al, 2013;Argany et al, 2012;Cortés et al, 2004), which are limited by the spatial resolution; and (ii) the methods that model the environment as a vector dataset (Ghosh and Das, 2006;Guvensan and Yavuz, 2011;Ma et al, 2009;Cao, 2006, 2011), which have been mostly proposed for 2D spaces and do not consider the earth topography and human-made obstacles. Furthermore, the sensing models (i.e., binary or probabilistic, omnidirectional or directional, etc.)…”
Section: Introductionmentioning
confidence: 99%